2019
DOI: 10.1002/ldr.3413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land management on soil erosion, connectivity, and sediment delivery in agricultural catchments: Closing the sediment budget

Abstract: Agricultural land, and arable farming in particular, is commonly associated with increased soil erosion risk. Such systems are most vulnerable during low groundcover periods, but downstream delivery is ultimately controlled by connectivity. This study provides a catchment‐scale sediment budget integrating three discrete but complementary investigations spanning different temporal and spatial scales. The first gives details on suspended sediment fluxes at the catchment outlet (2009–2012). The second provenances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The key controls for suspended sediment transport are soil type and land use. For example, arable farming on low permeability soils was particularly prone to sediment loss (Sherriff et al, 2019). The pathway for this transport was primarily through surface runoff driven by rainfall events, and thus catchment soil erosion risk can be classified according to soil drainage characteristics and land-use type (Sherriff et al, 2019).…”
Section: Sediment Loss and Aquatic Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…The key controls for suspended sediment transport are soil type and land use. For example, arable farming on low permeability soils was particularly prone to sediment loss (Sherriff et al, 2019). The pathway for this transport was primarily through surface runoff driven by rainfall events, and thus catchment soil erosion risk can be classified according to soil drainage characteristics and land-use type (Sherriff et al, 2019).…”
Section: Sediment Loss and Aquatic Ecologymentioning
confidence: 99%
“…For example, arable farming on low permeability soils was particularly prone to sediment loss (Sherriff et al, 2019). The pathway for this transport was primarily through surface runoff driven by rainfall events, and thus catchment soil erosion risk can be classified according to soil drainage characteristics and land-use type (Sherriff et al, 2019). Suspended sediment export from five of the six ACP catchments was low in comparison to values for the UK and mainland Europe.…”
Section: Sediment Loss and Aquatic Ecologymentioning
confidence: 99%
“…Harvey, 2002Harvey, , 2012Shook et al, 2021); alpine environments, which often involve debris flow activity (Berger et al, 2011;Cavalli et al, 2013;Croke et al, 2013;Heckman and Schwanghart, 2013;Turley et al, 2021); forested catchments and the role of roads and culverts (Galia et al, 2017); channel and floodplain relationships (Hooke, 2003;Sandercock and Hooke, 2011) and connectivity in semi-arid environments (Lesschen et al, 2009;Medeiros et al, 2010). Temperate lowland arable catchments have been somewhat neglected, though with some notable exceptions: Alder et al, 2015;Couturier et al, 2013;Gascuel-Odoux et al, 2009;Delmas et al, 2012;Sherriff et al, 2019;Souchere et al, 1998. In such catchments, each LE encountered by field-to-river flow and transported sediment may be located within a spectrum which ranges from the wholly natural in origin (e.g. the planform convergence of coarse-scale topography) to the wholly anthropogenic (e.g.…”
Section: Landscape Elements and Field-to-river Movement Of Runoff And...mentioning
confidence: 99%
“…Serious soil erosion on sloped farmland and ecological decline have resulted in environmental deterioration and reductions in the potential productivity of the soil (Zhao et al 2013;Huang and Zhao 2014;Huang 2017). Many studies have shown that other than rainfall characteristics, soil management practices are the primary factors influencing runoff generation and soil erosion (Truman et al 2007;Girmay et al 2009;Sherriff et al 2019). In order to promote the development of more sustainable agricultural practices on sloped farmland in this region, it is important to examine and implement effective soil management practices such as soil and water conversation (SWC) measures.…”
Section: Introductionmentioning
confidence: 99%